PENGARUH LITERASI KEUANGAN, SIKAP LOVE OF MONEY, DAN PENGETAHUAN LAPORAN KEUANGAN TERHADAP PERILAKU PENGELOLAAN KEUANGAN UMKM DI WILAYAH KABUPATEN SUBANG - Irwan Fathurrahman; Icih Icih; Asep Kurniawan (JASS (Journal of Accounting for Sustainable Society), 2020)
Many Micro, Small, Medium Enterprises (MSMEs) in Indonesia still do not conduct financial management behavior or there is no financial separation between business money and daily necessities. This study aims to determine the effect of financial literacy, love of money attitudes, and knowledge of financial statements on the behavior of financial management umkm in the Subang Regency. The population used in this research is MSME type of microbusiness in the area of ​​Subang Regency. The sampling technique used in this study is the "non-probability sampling" method and the sampling technique uses "purposive sampling". Samples taken as many as 120 people / respondents. The analytical tool used in this research is descriptive analysis, classic assumption test, and hypothesis testing using multiple regression. The results of this study indicate that financial literacy and attitude variables love of moneypartially positive and significant effect, while knowledge of financial statements is partially positive and not significant effect on financial management behavior. Then the three variables of financial literacy, the attitude of love of money and knowledge of financial statements simultaneously have a positive and significant effect on financial management behavior.